ARABIC-REQUIRING IMAMS OF MOSQUES TO RECITE A SPECIFIC RECITATION BETWEEN JURISPRUDENCE AND THE SAUDI SYSTEM - Faisal Abdulrahman Alshdi (دی اسکالر)
Research Subject:  The obligation of Masjids Imams to read and recite according to jurisprudence and the Saudi system.